Constitutive Models for Rubber IX proceedings of the 9th European Conference on Constitutive Models for Rubbers, (ECCMR IX), Prague, Czech Republic, 1-4 September 2015 - Marvalová, Bohdana; Petríková, Iva (CRC Press, 2015)
The 9th volume of Constitutive Models for Rubber, containing the papers presented at the the Ninth European Conference on Constitutive Models for Rubber (ECCMR 2015, Prague, Czech Republic, 1-4 September 2015), offers engineers, scientists and postgraduate students an overview of recent theoretical and experimental research on the behaviour, properties and modelling of rubber